Thiopurine analogues inhibit papain-like protease of severe acute respiratory syndrome coronavirus - Chou, Chi-Yuan (Biochem Pharmacol, 2008)
The papain-like protease of severe acute respiratory syndrome coronavirus (PLpro) (EC 3.4.22.46) is essential for the viral life cycle and therefore represents an important antiviral target. We have identified 6MP and 6TG as reversible and slow-binding inhibitors of SARS-CoV PLpro, which is the first report about small molecule reversible inhibitors of PLpro. The inhibition mechanism was investigated by kinetic measurements and computer docking. Both compounds are competitive, selective, and reversible inhibitors of the PLpro with K(is) values ∼10 to 20 μM. A structure–function relationship study has identified the thiocarbonyl moiety of 6MP or 6TG as the active pharmacophore essential for these inhibitions, which has not been reported before. The inhibition is selective because these compounds do not exert significant inhibitory effects against other cysteine proteases, including SARS-CoV 3CLpro and several cathepsins. Thus, our results present the first potential chemical leads against SARS-CoV PLpro, which might be used as lead compounds for further optimization to enhance their potency against SARS-CoV. Both 6MP and 6TG are still used extensively in clinics, especially for children with acute lymphoblastic or myeloblastic leukemia. In light of the possible inhibition against subset of cysteine proteases, our study has emphasized the importance to study in depth these drug actions in vivo.